Stylistic hybridity in palatial architecture during the reign of King Rama V: a postcolonial reinterpretation on modern Siam - Noobanjong, Koompong (My University, 2024)
Informed by postcolonial theories, this research presented critical investigations on Chakri Maha Prasat Throne Hall, the ordination hall at Niwet Thammaprawat Temple, and Munthatu Rattanaroj Villa. Aside from examining the three hybrid Siamese-European buildings beyond stylistic analyses and antiquarian mode of historiography, the upcoming discussions unveiled that the case studies–which were commissioned at the height of Western colonial expansions in Southeast Asia–testified for the Siamese’s: (1) reinterpretations, reappropriations, and recreations of European cultural artifacts; (2) active and authoritative roles in generating, combining, and projecting their versions of contested meanings upon the immediate world and beyond; (3) assertions of a newly acquired self-image by conspicuous consumptions of Western material culture; and (4) long established tradition of mediating power through built forms. In addition, by utilizing the politics of representations as a mode of problematization, these eclectic palatial structures were perceived as representational tools to create a civilized identity and discursive devices for power mediation, as opposed to unskilled or kitschy copies of Western precedents. In conclusion, the inquiries essentially argued that although Siam was among few places in Asia that did not succumb to a direct colonial rule by any Western power, the kingdom was a de facto crypto-colony.
Keywords: crypto-colonization in Siam; Hybrid buildings; palatial structures; politics of representations in architecture; postcolonial studies